CX-5461 is a potent immunosuppressant which inhibits T cell-mediated alloimmunity via p53-DUSP5. (March 2022) - Pan, Guopin; Zhang, Jing; Han, Yu; Chen, Ye; Guo, Xiaosun; Cui, Xiaopei; Cheng, Mei; Gao, Haiqing; Wang, Jianli; Jiang, Fan
Abstract: CX-5461 is a first-in-class selective RNA polymerase I inhibitor. Previously we found that CX-5461 had anti-inflammatory activities. In this study we characterized potential immunosuppressive effects of CX-5461 and explored the underlying mechanisms. Allogeneic skin transplantation model (BALB/c to C57BL/6 mice) and heterotopic heart transplantation model (F344 to Lewis rats) were used. We showed that CX-5461 was a potent inhibitor of alloimmunity which prevented acute allograft rejections. CX-5461 treatment was invariably associated with expansion of the regulatory T cell population. In vitro, CX-5461 inhibited agonists-induced T cell activation. CX-5461 consistently inhibited the expression of interferon-γ and interleukin − 2, key mediators of T cell-mediated alloimmunity. Mechanistically, CX-5461-induced immunosuppression was, at least partly, dependent on the p53-DUSP5 (dual-specificity phosphatase 5) axis and subsequent antagonism of the Erk1/2 mitogen-activated protein kinase pathway. In conclusion, our results suggest that CX-5461 is a promising candidate of a novel class of immunosuppressant which may be used as an alternative to the currently approved anti-rejection therapies. Graphical Abstract: ga1 Highlights: The selective RNA polymerase I inhibitor CX-5461 represses alloimmunity. CX-5461 prevents acute allograft rejection in two independent animal models. CX-5461 inhibits agonists-induced T cell activation in vitro and in vivo. Antagonism of Erk1/2 MAPK via p53-DUSP5 axis mediates CX-5461 effects. CX-5461 treatment also expands the regulatory T cell population. CX-5461 may be a promising candidate of a novel class of immunosuppressant.